The Chemopreventive Role of β-Elemene in Cholangiocarcinoma by Restoring PCDH9 Expression - Wu, Qing; Shi, Xintong; Pan, Yating; Liao, Xinyi; Xu, Jiahua; Gu, Xiaoqiang; Yu, Wenlong; Chen, Ying; Yu, Guanzhen (Frontiers in Oncology, 2022)
Background: β-elemene, an effective anticancer component isolated from the Chinese medicinal herb Rhizoma Zedoariae, has been proved to be therapeutic potential against multiple cancers in extensive clinical trials and experimental research. However, its preventive role in cholangiocarcinoma (CCA) and the mechanism actions of β-elemene on CCA need to be further investigated. Methods: A thioacetamide (TAA)-induced pre-CCA animal model was well-established and low dosage of β-elemene was intragastrically (ig) administered for 6 months. Livers were harvested and examined histologically by deep-learning convolutional neural network (CNN). cDNA-array was used to analyze the genetic changes of CCA cells following β-elemene treatment. Immunohistochemical methods were applied to detect β-elemene-targeted protein PCDH9 in CCA specimens and its predictive role was analyzed. β-elemene treatment in cellular or animal level was performed to test the effect of this traditional Chinese medicine on CCA cells. Results: In the rat model of pre-CCA, the ratio of cholangiolar proliferation lesions was 0.98%±0.72 in the control group, significantly higher than those of the β-elemene (0. 47%±0.30) groups (P=0.0471). KEGG pathway analysis showed that the top 10 pathways affected by β-elemene treatment were associated with energy metabolism and one was associated with cell cycle. β-elemene inactivated a number of oncogenes and restored the expression of multiple tumor suppressors. PCDH9 is a target of β-elemene and displays an important role in predicting tumor recurrence of CCA patients. Conclusions: These findings proved that long-term use of β-elemene has a potential to interrupt the progression of CCA and improve the life quality of rats. Moreover, β-elemene exerted its anti-cancer potential partially via restoring the expression of PCDH9.